Synthesis, anticancer activities and experimental-theoretical DNA interaction studies of 2-amino-4-phenyl-4H-benzo[h]chromene-3-carbonitrile - Taniris Cafiero Braga; Marina Magalhães Silva; Eduarda O.O. Nascimento; Edjan Carlos Dantas da Silva; Yuri de Freitas Rego; Mullicka Mandal; Zaqueu Alves de Souza; Ana Lúcia Tasca Góis Ruiz; João Ernesto de Carvalho; Felipe Terra Martins; Isis Martins Figueiredo; Thiago Mendonça de Aquino; et al. (Elsevier, 2022)
Twenty chromenes were synthesized with good to excellent yields (70-96%). From the series of chromenes herein tested, compounds 14, 12, 15, 16, 17, 18, and 20 were the most potent throughout the cancer human cell lines tested. In general, the para-position electron-withdrawing substituents on the phenyl ring are favored towards potency and selectivity for cancer cells. Biophysical studies were performed with eight chromene derivatives (13-20) and ctDNA to evaluate possible biological targets. The molecular fluorescence verified that compound 16 presented a higher binding constant (Kb) with the ctDNA, agreeing with in vitro biological results and that evaluated chromenes derivatives interact preferentially via intercalation. Finally, an inverse linear correlation (logKb vs. GI50) was observed for six human carcinogenic cell lines; hence, the mechanism of action of these compounds may be related to DNA interaction.